The production of the space. Territory and participatory management - Iglesias Montero, Gerardo; Alonso Freyre, Joaquín; Martínez Iglesias, Marisol Isabel (Revista Universidad de Guayaquil, 2016)
Territories and societies are complex, as they are constituted and intervened by a multiplicity of elements and factors of different nature: natural, social, political, economic, cultural, legal, technological, ethnic, religious, among others. These factors go through and characterize the living and working conditions of human settlements that occupy a certain geographical space at a given historical moment. For its part, participatory management does not invoke a new participation model or a new type of participation, which is intended to be managed through participation. It is the obtaining of a result from the active involvement of those social actors who have experience on the particular object. The participative management of the geographical space is based on the contribution of the people who have a link - understood this by knowledge or experience - with the territory, either from the coexistence or from the administration. It is assumed that all individuals have knowledge of the place they inhabit which has been given by empirical experience. In fact, permanence may be an element to be taken into account for more favorable management. However, mobility and scientific knowledge are factors that facilitate more effective information on the interactions that occur in the territory. Collective intelligence may provide the necessary knowledge to determine the actions that must be undertaken in local development projects.
Keywords: space; territory; participation; participative management